Body image, body mass index and the experience of Hiya in physical education among Filipino female university students - Brebante, Zyra Ruth T.; Cagas, Jonathan Y. (2015)
Body image dissatisfaction has been found to be associated with either high or low body mass index (BMI) among Filipino women (Aquino et. al. 2009). Hiya, a very distinct Filipino characteristic that may be referred to, but not necessarily equivalent to shame, may be experienced by a person who has high body image dissatisfaction which may then become a barrier to physical activity participation. The relationships between body image, BMI, and hiya have not been explored in previous literature. Therefore, the purpose of this present study is to examine the relationships between body image, BMI, and hiya in the context of physical education (PE). Three hundred sixty-two female Filipino university students answered a set of questionnaires which included the Modified Body Self-Image Questionnaire (BSIQ: Rowe 1999) and a measure of hiya designed specifically for this study. BMI was computed from one-site measured height and weight. results of correlation analyses indicated significant relationships between body image and BMI. More specifically, female students who had higher BMI evaluated their health/fitness and appearance negatively, had higher perception of fatness, and had more negative feelings towards their bodies. Results also showed significant relationships between body image and hiya in PE. female students with high perception of their overall appearance and health/fitness experience less hiya in PE.
Keywords: Body image in women -- Attitudes; Body mass index; Women college students